Assessing the Impact of Oil Shocks on Banking Liquidity Indicators in Iraq: For the Period 2015-2024 - Jinan Salim Hilal (Research Parks Publishers, 2026)
This research examines how oil shocks, both positive and negative, affected banks liquidity indicators, which drive Iraq's financial activity. Iraqi indices for 2015–2024: liquid asset to total asset, short-term liabilities, and client deposit to total loan ratios. Data is released annually. Modern econometric approaches were utilised to study economic variables and their time series. Stationarity, cointegration (with the boundary approach), VECM, and ARDL statistical models were utilised. Negative oil shocks correlate directly with bank liquidity metrics, the data show. Iraq's economy relies on oil income for over 85% of its revenue, making it sensitive to shocks. The findings show that negative shocks affect the indices more than positive ones. Study results and suggestions are its conclusion.